The Effectiveness of Stem-PjBL on the Ability to Think Critically in the Context of Pletok Beer as a Traditional Drink to Support Health in the Digestive System - Desy Indrias Wari; Paidi; Suyitno Aloysius (Postgraduate, University of Mataram, 2025)
This study aims to evaluate the effectiveness of the Science, Technology, Engineering, and Mathematics Project-Based Learning (STEM-PjBL) model in enhancing students' critical thinking skills through the contextual integration of bir pletok, a traditional beverage known for supporting digestive health. A systematic literature review (SLR) was conducted using the PRISMA 2020 protocol, analyzing 30 scientific articles that met defined inclusion criteria. The analysis revealed that STEM-PjBL significantly improves students' critical thinking, particularly in the domains of analysis, evaluation, and inference. Incorporating bir pletok as a learning context provided authentic, culturally relevant experiences that bridged scientific concepts with local wisdom. Key factors influencing learning success included the use of technology, personalized learning strategies, and the integration of indigenous knowledge. These findings contribute both theoretically and practically to the design of holistic and contextual 21st-century learning models that are sustainable and culturally responsive.